Recapitulating Zika Virus Infection in Vagina of Tree Shrew (Tupaia belangeri) - Baloch, Zulqarnain; Shen, Zhili; Zhang, Li; Feng, Yue; Li, Daoqun; Zhang, Na-Na; Deng, Yong-Qiang; Yang, Chunguang; Sun, Xiaomei; Dai, Jiejie; Yang, Zifeng; Qin, Cheng-Feng; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Sexual transmission of Zika Virus (ZIKV) elevates the risk of its dissemination in the female reproductive tract and causes a serious threat to the fetus. However, the available animal models are not appropriate to investigate sexual transmission, dynamics of ZIKV infection, replication, and shedding. The use of tree shrew as a small animal model of ZIKV vaginal infection was assessed in this study. A total of 23 sexually mature female tree shrews were infected with ZIKV GZ01 via the intravaginal route. There was no significant difference in change of body weight, and the temperature between ZIKV infected and control animals. Viral RNA loads were detected in blood, saliva, urine, and vaginal douching. ZIKV RNA was readily detected in vaginal lavage of 22 animals (95.65%, 22/23) at 1 dpi, and viral load ranged from 104.46-107.35 copies / ml, and the peak of viral load appeared at 1 dpi. The expression of key inflammatory genes, such as IL6, 8, CCL5, TNF-a, and CXCL9 was increased in the spleen of ZIKV infected animals. In the current study, female tree shrews have been successfully infected with ZIKV through the vaginal route for the first time. Interestingly, at first, ZIKV replicates at the local site of infection and then spreads throughout the host body to develop a robust systemic infection and mounted a protective immune response. This small animal model is not only valuable for exploring ZIKV sexual transmission and may also help to explain the cause of debilitating manifestations of the fetus In vivo.